Urban Resident Views About Open Green Spaces: A Study in Güzelyurt (Morphou), Cyprus - Yıldırım, Sinem; Asilsoy, Buket; Özden, Özge (European Journal of Sustainable Development, 2020)
A dramatic demographic shift regarding urbanization is occurring globally. Between 2000 and 2050, the ratio of individuals in urban spaces is projected to rise from 46.6 % to 69.6%. Environmental pollution, urban heat island effect and climate change are among the hazardous effects of urbanization. Critical ecosystem services can be provided with urban green areas such as parks, roof gardens, streams, forests and community gardens etc. Walking, running or biking activities, psychological well-being and public health of urban inhabitants can also be supported via green space. Urban landscape areas are also significant for Cyprus as there is an on-going remarkable urbanization. Particularly, due to urbanization, the importance of green spaces in cities is becoming important. During this study, open and green space as urban landscape areas in Güzelyurt (Morphou) was investigated. This is the first study to examine user satisfaction and views of open and green spaces in Güzelyurt (Morphou) region, Cyprus. A questionnaire with 60 participants were conducted in order to understand respondents’ suggestions about several aspects of existing open and green spaces in Güzelyurt, north Cyprus. According to the findings, respondents were mostly dissatisfied about urban and open spaces in the city. Our results indicate that local authorities or municipal organizations should legalize the planning of urban parks, open spaces and green areas with long term perspective. Keywords: Urbanization, Green space, urban park, landscape, Güzelyurt, Cyprus